2008
DOI: 10.1007/s12192-008-0039-z
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock proteins HSP70 and HSP27 in the cerebral spinal fluid of patients undergoing thoracic aneurysm repair correlate with the probability of postoperative paralysis

Abstract: An understanding of the time course and correlation with injury of heat shock proteins (HSPs) released during brain and/or spinal cord cellular stress (ischemia) is critical in understanding the role of the HSPs in cellular survival, and may provide a clinically useful biomarker of severe cellular stress. We have analyzed the levels of HSPs in the cerebrospinal fluid (CSF) from patients who are undergoing thoracic aneurysm repair. Blood and CSF samples were collected at regular intervals, and CSF was analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Increases in serum ehsp70 concentrations occur in various systemic inflammatory conditions such as Behςet’s disease and rheumatoid arthritis, but the role of ehsp70 in central nervous system (CNS) inflammation requires investigation. An ehsp70 response in autoimmune disease of the CNS has not been evaluated, although sustained ehsp70 release is described in the inflammatory sequel to ischemia-reperfusion injury of the spinal cord in dogs and humans (Awad et al, 2008; Hecker et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Increases in serum ehsp70 concentrations occur in various systemic inflammatory conditions such as Behςet’s disease and rheumatoid arthritis, but the role of ehsp70 in central nervous system (CNS) inflammation requires investigation. An ehsp70 response in autoimmune disease of the CNS has not been evaluated, although sustained ehsp70 release is described in the inflammatory sequel to ischemia-reperfusion injury of the spinal cord in dogs and humans (Awad et al, 2008; Hecker et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the realm of neuroprotection, Hsp70 might be a useful target molecule for the therapeutic treatment. Previous studies have demonstrated that the induction of Hsp70 may be responsible for secondary processes after SCI [38,39]. Recent experimental evidence showed that upregulation of Hsp 70 with pharmacological inhibition of inflammation achieved a neuroprotective effect [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Release of hsp70 into cerebrospinal fluid (CSF) of the central nervous system (CNS) is an emerging field of research. Increased hsp70 levels in CSF have been reported in association with the inflammatory response to ischemia-reperfusion injury in spinal cords of humans and dogs [92,93]. Data from the ischemic-reperfusion injury model in dogs supports secretory release from within the CNS since hsp70 levels in serum was unaffected [92].…”
Section: Extracellular Hsp70mentioning
confidence: 99%